1987
DOI: 10.1111/j.1476-5381.1987.tb11363.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ouabain on tension in isolated respiratory tract smooth muscle of humans and other species

Abstract: 1The Na', K+-pump has been implicated in animal models of airway hyperreactivity. We examined the effects of inhibiting the Na', K+-pump and Na+, Ca2+-exchange on isometric tone of isolated trachealis from humans and other species. 2 In preparations from 5 out of 9 humans, strong spontaneous contractions (36-48 h-'; up to 1.8 g) developed within 25 min. 3 Ouabain (10-7-10-'M) caused an immediate and sustained contraction. This response was not blocked by atropine, diphenhydramine, or cimetidine. 4 Contractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2

Year Published

1989
1989
1995
1995

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 13 publications
3
27
2
Order By: Relevance
“…Al though it is known that an active electrogenic pump is present in the smooth muscle of the guinea pig and bovine airway (19), it remains to be determined whether the Na+ electro genic pump is present in the canine trachea. It has been reported that a K+-free solution has no effect on the isolated canine trachea (5). In the present study, the tracheal con striction that remained after bilateral vagotomy was almost completely abolished by atropine.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Al though it is known that an active electrogenic pump is present in the smooth muscle of the guinea pig and bovine airway (19), it remains to be determined whether the Na+ electro genic pump is present in the canine trachea. It has been reported that a K+-free solution has no effect on the isolated canine trachea (5). In the present study, the tracheal con striction that remained after bilateral vagotomy was almost completely abolished by atropine.…”
Section: Discussionsupporting
confidence: 63%
“…Tracheal constriction occurred at a total dose of 45.0±5. 5 ag/kg (n=5) of ouabain. When the total dose of ouabain reached 54.4±6.1 ug/kg (n=5), a decrease in heart rate occurred.…”
Section: Effects Of Ouabain Administeredmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect, not observed by , was seen by Chideckel et al (1987). It is possible that, in our experiments, hyperpolarization in K+-free MKH has a greater initial effect on membrane potential than depolarization resulting from inhibition of electrogenic pump current (Fleming, 1980).…”
Section: Concentration-response Curvesmentioning
confidence: 58%
“…;et al, 1982). A more recent report showed that spontaneous contraction developed in 4 out of 5 human tissues, within 25 min of the start of tissue incubation in an organ bath (Chideckel et al, 1987). However, in these two studies, the human tracheal tissue originated mainly from cadavers.…”
Section: Introductionmentioning
confidence: 97%